Improving plant salt tolerance through Algoriphagus halophytocola sp. nov., isolated from the halophyte Salicornia europaea - Peng, Yuxin; Cho, Dong Hyun; Humaira, Zalfa; Park, Yu Lim; Kim, Ki Hyun; Kim, Cha Young; Lee, Jiyoung (Frontiers in Microbiology, 2024)
Salicornia europaea, commonly known as glasswort, thrives in reclaimed land and coastal areas with high salinity, demonstrating remarkable adaptation to the arid conditions of such environments. Two aerobic, Gram-stain-negative, non-motile, rod-shaped bacterial strains, designated TR-M5 T and TR-M9, were isolated from the root of Salicornia europaea plants. These bacteria exhibit plant growthpromoting and salt tolerance-enhancing abilities, which have not been reported in other species of the genus. Both strains produce indole-3-acetic acid (IAA), a plant growth hormone, and synthesize proline, which functions as an osmoprotectant. Additionally, they possess gelatinase and cellulase activities. Cells grow in temperatures from 4°C to 42°C (optimum 25°C), pH levels from 6.0 to 9.0 (optimum 7.0), and NaCl concentrations from 0% to 8.0% (optimum 6.0%). The average nucleotide identity and digital DNA-DNA hybridization values of strain TR-M5 T with the most closely related type strains for which whole genomes are publicly available were 74.05%-77.78% and 18.6-23.1 %, respectively. Phylogenetic analysis of their 16S rRNA gene sequences revealed that strains TR-M5 T and TR-M9 belong to the genus Algoriphagus. A. locisalis exhibited the highest similarity, sharing a sequence identity of 98.1%. The genomes of TR-M5 T and TR-M9 exhibit a G + C content of 43 mol%. This study specifically focuses on the identification and characterization of strain TR-M5 T as a novel species within the genus Algoriphagus, which we propose to name Algoriphagus halophytocola sp. nov., highlighting its potential role in enhancing plant growth and salt tolerance in saline environments.